Plantar aponeurosis features according to the results of anatomical research - Turchin, Olena; Hrygorovska, Anastasiia; Snisarevskiy, Pavlo; Lyabakh, Andriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2020)
Objective: analysis of the results of plantar aponeurosis anatomy, clarification of its structural features and linear sizes. Methods: we studied the anatomy of plantar aponeurosis of the 20 fresh amputated lower limbs. The average age of patients (15 men, 5 women) was (53.5 ± 18) years old. Diseases that have become cause of amputations were oncological — 10, obliterating angiopathy — 5, consequences of injuries — 5. Using vernier caliper we measured the linear dimensions (mm) of the plantar aponeurosis: length, proximal and distal width, width of lateral and central bundles, thickness of the proximal aponeurosis and the lateral bundle. Average values were calculated. Results: plantar aponeurosis consisted of well-defined, longitudinally located bundles; fan-shaped expanded from the narrow proximal part with a width of (26.8 ± 5.4) mm to a wide distal — (71.9 ± 3.2) mm. Mid plantar length aponeurosis was (128.0 ± 16.8) mm. Thickness enthesis — (3.6 ± 1.9) mm. The medial bundle was not expressed and formed with the central one. Width of the central bundle amounted to (15.35 ± 1.50) mm. Lateral, thinner bundle, in 17 cases was well defined, its width was (11.75 ± 2.70) mm, thickness — (2.25 ± 1.06) mm. In three cases the lateral bundle was reduced from the calcaneus. Options for the absence of the lateral bundle were not detected. Conclusions: plantar aponeurosis — fan-shaped structure with shiny white color consists of well-defined, longitudinally located bundles. Three-beam plantar aponeurosis structures were not observed after moving away from the calcaneal tuber. The central bundle of the aponeurosis is the widest and thickest, thinner lateral was of varying severity, in three cases, gradually reduced. The medial bundle, which forms a single structure with the central bundle, turned out to be the most subtle and not expressed.